PENGEMBANGAN HANDOUT BERBASIS KONTEKSTUAL PADA MATERI SISTEM PERNAPASAN MANUSIA UNTUK TINGKAT SMP - Iklima, Iklima; Ardi, Ardi; Risdawati, Renny (STKIP PGRI Sumbar, 2013)
ABSTRACTLearning process is the core process of formal education in schools where teaching interaction (teacher, subject matter, and students) is a major component, includedÂ infrastructure. Among of these components, the teacher is the main play of which is the learning planner (design proper teaching materials and fun). One of these materials is handout based contextual. This research aims to produce of valid and practical handout based contextual on the human respiratory system materials for Junior High Schools. This research is a development research which refers to the 4-D models. The result of this research is handout based contextual that developed had valid and very practical criteria.Â Â